LD MEMBANGUN ORGANISASI FORMAL: TAHAPAN STRATEGIS KEMENAG DALAM MENINGKATKAN EFEKTIVITAS LAYANAN PUBLIK - Ilham Ansori; Suparto (MADDINA: Jurnal Manajemen Dakwah, 2024)
Formal organizations play an important role in improving the quality of public services, especially in government institutions. This article discusses the strategic stages of formal organizational structuring at the Ministry of Religious Affairs (Kemenag) and its impact on the effectiveness of public services. Through literature analysis and empirical data, this research finds that a well-planned organizational structure can enhance efficiency, accountability, and public satisfaction. Internal and external obstacles affecting the process are also reviewed to provide practical recommendations for bureaucratic reform.